Weathering study of the gneissic rock mass from the Monte Seco tunnel region, southeastern Brazil. - Monticelli, João Paulo (2019)
This study refers to a qualitative and quantitative weathering characterization of a gneiss rock mass (weathering profile, intact rock and discontinuity) in a tropical region. The rock mass was excavated for a construction of an unlined railway tunnel, which during its useful life began to present block instability problems linked to the weathering and the time of exposure of the rock. The weathering of the rock mass and its weathering grades are approached in the geological and geotechnical points of view, covering bibliographical review on the subject, field inspection, direct and indirect investigations, and laboratory tests: petrographic analysis, X-ray diffraction, physical properties and durability index, sclerometry, ultrasonic test, uniaxial and diametral compression.